Functional Connectivity Patterns Associated with Inflammation in Psychosis; Results From the UK Biobank Database - Edward Palmer; Rachel Upthegrove; Jack Rogers (BJPsych Open)
Aims: Recent evidence suggests that inflammation and immune dysregulation play a role in mental health disorders, including psychosis. Research has identified grey matter volume changes, however, the relationship between inflammation and functional connectivity remains underexplored. This study investigates the impact of CRP levels on functional connectivity in psychosis.